Thickness effects of myofibrillar protein based edible films on their functional properties - Sobral, Paulo José do Amaral (Pesquisa Agropecuaria Brasileira, 2000)
Research on edible and biodegradable films had been promoted recently because of environmental concerns. The use of these materials for packaging applications is conditioned by their functional properties, which are influenced by many factors, including thickness. The objective of this work was to study the influence of thickness of myofibrillar protein-based biofilms on some of their functional properties. Biofilms were prepared from film forming solutions (FFS) containing 1 g of protein/100 g of FFS. The plasticizer concentration was 45 g glycerin/100 g of protein and the pH was kept at 2.7. After drying, biofilms were conditioned in desiccators at 58% relative humidity and 22ºC, for four days. Mechanical properties were determined by puncture tests; water vapor permeability, using a gravimetric method, and color and opacity, with a HunterLab colorimeter, all tests at 22ºC. Tensile strength, water vapor permeability, color and opacity of both biofilms, increased linearly upon thickness. Deformation at break presented little slope with considerable points dispersion for both biofilms. Water vapor transmission rate decreased linearly with thickness.